1990
DOI: 10.1159/000168084
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Congestive Heart Failure, Dilated Cardiomyopathy, Hypertrophic Hyperkinetic Disease, and Ischemic Heart Disease in Dialysis Patients

Abstract: Congestive heart failure in dialysis patients is associated with dilated cardiomyopathy, hypertrophic hyperkinetic disease and ischemic heart disease. To determine the natural history of these four diseases, 150 dialysis patients were prospectively followed for 3–5 years. The 2-year cumulative survival rate was 33% in those with recurrent or persistent congestive heart failure vs. 80% in dialysis patients without. Survival was significantly worse in patients with an echocardiographic diagnosis of dilated cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…LVH is present in >70% of patients with ESRD [13]and is an important factor for the development of cardiovascular events. Furthermore, LVH is an adverse prognostic factor in patients with ESRD [13, 14, 15]. Therefore, improving LVH and preventing the development of LVH is very important in the management of ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…LVH is present in >70% of patients with ESRD [13]and is an important factor for the development of cardiovascular events. Furthermore, LVH is an adverse prognostic factor in patients with ESRD [13, 14, 15]. Therefore, improving LVH and preventing the development of LVH is very important in the management of ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that patients on HD have a higher cardiovascular morbidity and mortality [20], The contri bution of the HD process itself to the development of myocardial ischemia is less well known. We had previous ly shown that STD, a possible marker for myocardial isch emia developed in association with dialysis in nearly half the patients studied [10], While STD usually signals myocardial ischemia, we and others have raised the concern that, being an 'elec trical phenomenon', it may result from the electrolyte shifts which occur during dialysis [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases are the main cause of death in chronic renal failure [1] . Many risk factors can predict the mortality of these patients, and most of them are related to cardiovascular status [5][6][7] .…”
mentioning
confidence: 99%